Demonstrating Value: A Draft Framework for Evaluating the Effectiveness of Career Development Interventions - Baudouin, Robert; Bezanson, Lynne; Borgen, Bill; Goyer, Liette; Hiebert, Bryan; Lalande, Vivian; Magnusson, Kris; Michaud, Guylaine; Renald, Cï¿½line; Turcotte, Michel (Canadian Journal of Counselling and Psychotherapy, 2008)
The findings from recent Canadian research indicate that while agency managers and front-line workers agree that evaluation is important, they seldom evaluate their work with clients. With the current emphasis on evidence-based practice and outcome-focusedintervention, it is important to be able to demonstrate the value of career services in a manner that service providers find meaningful and funders find useful. In this article a framework for evaluation is presented that permits linking the services provided with the client outcomes that are being achieved.